Does Stigma Moderate the Efficacy of Mental- and Behavioral-Health Interventions? Examining Individual and Contextual Sources of Treatment-Effect Heterogeneity. (December 2021) - Hatzenbuehler, Mark L.; Pachankis, John E.
In this article, we argue that stigma may be an important, but heretofore underrecognized, source of heterogeneity in treatment effects of mental- and behavioral-health interventions. To support this hypothesis, we review recent evidence from randomized controlled trials and spatial meta-analyses suggesting that stigma may predict not only who responds more favorably to these health interventions (i.e., individuals with more stigma experiences), but also the social contexts that are more likely to undermine intervention effects (i.e., communities with greater structural stigma). By highlighting the potential role of personal and contextual stigma in shaping response to interventions, our review paves the way for additional research.